The Capability Approach in physical activity promotion: Using the example of the BIG project Der Capability-Ansatz in der Bewegungsförderung: Das Beispiel des BIG-Projekts - Till, Maike; Abu-Omar, Karim; Gelius, Peter (Pravention und Gesundheitsforderung, 2022)
Background: The empowerment of different target groups and the reduction of health inequalities are a main focus of many health promotion projects. However, determinant and empowerment approaches, which are often used as theoretical basis for such projects, have a number of drawbacks. Recently, the Capability Approach (CA) has been increasingly employed as a potential alternative. To date, however, only few studies have investigated the benefits of this approach and its applicability in health promotion. Objective: The aim of this paper is to demonstrate how the CA can be used for the ex-post evaluation of physical activity promotion projects, how it demonstrates intervention effects in different areas, and how it helps link them to each other. Methods: We used the BIG-Project, targeting socially disadvantaged women across different settings, as an example for employing the CA. For the evaluation, we systematically analyzed n = 37 project documents published over a 16-year period. Results: Categorizing BIG into the capability model highlights the broad spectrum of effects of a participatory intervention for physical activity on different levels. The approach also demonstrates the links between structure and agency for physical activity as well as between the “target group” and setting professionals/policymakers. Conclusion: The CA facilitates the systematic evaluation of intervention effects on structures and agency, focusing both on the individual and the collective level. As such, it provides an opportunity to systematically link empowerment and determinant approaches and to use them for evaluating projects aimed at the reduction of health inequalities.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Capability approach; Empowerment; Health promotion; Participation; Physical activity